Kerugian Keuangan Negara atau Perekonomian Negara Dalam Menentukan Hukuman Mati Pada Tindak Pidana Korupsi - Herman Katimin (Faculty of Law, Universitas Pattimura, 2020)
The difficulty of capital punishment for perpetrators of corruption, although there are several examples of corruption cases that have fulfilled certain elements of the conditions as Article 2 paragraph (2) of Law Number 20 of 2002 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes. To discuss this problem, the research method used is juridical normative relating to certain elements of the state and the amount of state financial losses or the state's economy in determining the death penalty. The results of the discussion included not explaining the specific elements of certain circumstances as a burden for corruptors. In addition, the amount of state financial losses or the country's economy is very important in determining the death penalty is not formulated in certain circumstances. Therefore, it is recommended that specific formulations of certain elements and the amount of state financial losses or state economies that reach billions of up to triulian rupiah be subject to the death penalty.